The Impact of International Climate Agreements on Environmental Policy in Punjab (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper examines the influence of international climate agreements, most notably the UN Framework Convention on Climate Change (UNFCCC) and the Paris Agreement, on environmental policy formulation and implementation in Punjab in India. By analyzing ways in which global commitments, normative pressure, technical guidance, financial & technological support, legal & political commitments, etc., influence the sub-national level governance systems and policies, the study reveals the ways in which the state of Punjab has absorbed international climate commitments in its sub-national level initiatives. Key areas of policy alignment include areas such as renewable energy adoption, air quality management, climate resilient agriculture, water resource management, and public capacity building programs. Despite these efforts, there are still challenges in getting international goals to effective local action, given the aspect of fragmented governance, lack of resources, socio-economic trade-offs, political fluctuations, and behavioral barriers. The research highlights that although the state of Punjab is demonstrating considerable alignment to global climate frameworks to achieve comprehensive environmental outcomes, this would necessitate better institutional coordination, sustained political will, greater access to international funding and technology, and more specific public engagement. The paper concludes with recommendations for enhancing the climate governing structures in Punjab, so that international climate commitments effectively provide the basis for sustainable local adaptation policy balancing environmental, economic, and social goals.